Enhancing TVET Education Through Communication Skills (2015 2025): A Systematic Review of Workplace Needs - RASHID ALI, FARRAH DIEBAA; ABD HAMID, MOHD AZRUL AZLEN; AHMAD, KHALILULLAH AMIN (2025)
As Malaysia advances towards industrialisation, Technical and Vocational Education and Training (TVET) plays a central role in preparing a skilled workforce. While TVET graduates are recognised for their technical expertise, employers consistently report deficiencies in communication skills, which limit workplace performance and career growth. To inform educational improvement, this review synthesises studies published between 2015 and 2025 to examine the importance of communication skills in Malaysian TVET workplaces and the functional conditions necessary for their effective application. Using the PRISMA framework, a systematic literature review of 400 articles was conducted through Google Scholar and Elicit, with eight empirical studies meeting the inclusion criteria. Data drawn from 148 field experts and 10 academic experts across engineering, construction, hospitality, cosmetology, and agriculture reveal three dimensions of importance: (i) organisational benefits, (ii) operational efficiency, and (iii) employability and career progression. Five functional conditions were also identified: general language proficiency, technical vocabulary, genre-appropriate communication, sensitivity to regional variations, and non-verbal competence. The findings confirm communication as integral, not supplementary, to TVET workplace success. However, gaps remain in linking communication skills to measurable performance outcomes and embedding them systematically in curricula. Addressing these gaps is vital for enhancing graduate employability, advancing Malaysia’s TVET Policy 2030, and achieving sustainable socio-economic development.